2023
DOI: 10.1088/1741-4326/acd394
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of the molecular charge-exchange rate on detached SOLPS-ITER simulations

Abstract: Plasma-molecular interactions generate molecular ions which react with the plasma and contribute to detachment through molecular activated recombination (MAR), reducing the ion target flux, and molecular activated dissociation (MAD), both of which create excited atoms. Hydrogenic emission from these atoms have been detected experimentally in detached TCV, JET and MAST-U deuterium plasmas. The TCV findings, however, were in disagreement with SOLPS-ITER simulations for deuterium indicating a molecular ion densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…We find that MAR does not play a significant role in our simulations. However, we note that MAR (as well as molecular activated dissociation-MAD), involving D + 2 , may be underestimated in SOLPS-ITER as the reaction rates are specified for hydrogen and in certain cases re-scaled to deuterium using a simplified mass re-scaling [27,28]. As one would expect, a higher divertor electron density and lower plasma temperature near the target is achieved in the fuelling scan.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…We find that MAR does not play a significant role in our simulations. However, we note that MAR (as well as molecular activated dissociation-MAD), involving D + 2 , may be underestimated in SOLPS-ITER as the reaction rates are specified for hydrogen and in certain cases re-scaled to deuterium using a simplified mass re-scaling [27,28]. As one would expect, a higher divertor electron density and lower plasma temperature near the target is achieved in the fuelling scan.…”
Section: Introductionmentioning
confidence: 93%
“…Non selfconsistent post-processing of these simulations has been performed for diagnostic purposes in [25], which showed that this does not play a significant role in the seeded simulations, but plays a significant role in the density ramp cases after the detachment onset; resulting in significant levels of MAR, hydrogenic emission and MAD-leading to plasma energy losses and additional neutral atoms. This post-processing, which is not self-consistent, is expected to exaggerate the molecular effects by roughly ×2 [28]. It is possible that repeating this study with updated ion-conversion cross-sections may change the solutions discussed in this work such that ionconversion plays a more significant role.…”
Section: Impact Of D + − D 2 Elastic Collisions On Energy Andmentioning
confidence: 99%
See 3 more Smart Citations